The Selection of the Practice of Ice Canoeing on the St. Lawrence River: Birth of a Nomination - Genest, Bernard (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
The purpose of this article is precisely to outline in what manner and circumstances the Quebec Society of Ethnology came to make the request to the Quebec ministry of Culture for recognition of the practice of ice canoeing. In fact, ice canoeing was the second practice to be listed on the Quebec register on intangible cultural heritage since its institution in 2012. The author points out that the process is not as simple as might be assumed, and it is fortunate that the designation in terms of the Quebec Cultural Heritage Act, adopted in 2012, is not a trivial measure. It involves the minister’s giving status to a part of the intangible heritage of which knowledge, safeguarding, promotion or transferral is in the public interest.